Transforming Growth Factor Alpha (TGF-α) and Other Targets of Tumor Necrosis Factor-Alpha Converting Enzyme (TACE) in Murine Polycystic Kidney Disease - NEMO, RAGHAD (2005)
Transforming growth factor-alpha (TGF-α) is abnormally expressed in autosomal recessive polycystic kidney disease (ARPKD). Tumor necrosis factor-alpha converting enzyme (TACE), a metalloproteinase, mediates TGF-α processing. In this study, we sought to determine whether TGF-α was an absolute requirement for renal cystogenesis and whether its absence would modulate disease severity or related growth factors/receptors expression. Bpk heterozygotes were bred with TGF-α null mice to produce cystic and noncystic offspring with or without TGF-α. Assessments included kidney weight (KW), body weight (BW), blood urea nitrogen (BUN), and kidney and liver immunohistology. Western analysis assessed kidney expression of amphiregulin (AR), epidermal growth factor (EGF), heparin-binding EGF (HB-EGF), and their receptors, EGFR and ErbB4. A PCR-based methodology for genotyping bpk mice was also developed. No significant differences in KW, BW, KW/BW%, or BUN were seen in cystic mice with versus without TGF-α. Cystic kidney disease and liver disease histology were similar. AR, EGF, HB-EGF, EGFR, and ErbB4 were abnormally expressed to an equal degree in kidneys of mice with versus without TGF-α. Although previous data suggest a critical role of TGF-αin murine PKD, these data show that TGF-αis not required for renal cyst formation or kidney or liver disease progression. We speculate that the therapeutic effect of WTACE2 could have been due to effects on several TACE targets, including TGF-α, AR, and ErbB4, as well as metalloproteinases other than TACE.